2021
DOI: 10.1093/ofid/ofab452
|View full text |Cite
|
Sign up to set email alerts
|

A High Frequency of Candida auris Blood Stream Infections in Coronavirus Disease 2019 Patients Admitted to Intensive Care Units, Northwestern India: A Case Control Study

Abstract: Background The ongoing pandemic of COVID-19 has overwhelmed healthcare facilities raising an important novel concern of nosocomial transmission of Candida species in the intensive care units. Methods We evaluated the incidence and risk factors for development of candidemia in 2384 COVID-19 patients admitted during August 2020-January 2021 in ICUs of two hospitals (Delhi and Jaipur), India. A 1:2 case control matching was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 43 publications
5
41
1
3
Order By: Relevance
“…Thus, the ongoing COVID‐19 pandemic would become a perfect battlefield for outbreaks of C. auris because of the similar underlying diseases and the risk factors, which increases the chance of C. auris infections in COVID‐19 patients. Further, a recent study from India confirmed these findings, that the treatment with interleukin‐6 antagonists such as tocilizumab, prolonged ICU stay, mechanical ventilation and raised ferritin levels were identified as significant risk factors of candidemia (majority of reported cases in the study were due to C. auris ) in COVID‐19 patients 36 …”
Section: Discussionsupporting
confidence: 53%
“…Thus, the ongoing COVID‐19 pandemic would become a perfect battlefield for outbreaks of C. auris because of the similar underlying diseases and the risk factors, which increases the chance of C. auris infections in COVID‐19 patients. Further, a recent study from India confirmed these findings, that the treatment with interleukin‐6 antagonists such as tocilizumab, prolonged ICU stay, mechanical ventilation and raised ferritin levels were identified as significant risk factors of candidemia (majority of reported cases in the study were due to C. auris ) in COVID‐19 patients 36 …”
Section: Discussionsupporting
confidence: 53%
“…Further to this, ours is the first study in which isolates causing candidemia during the COVID-19 pandemic have been genotyped to gain more insight about patient-to-patient transmission not only in patients with COVID-19 but also in patients with candidemia and non-COVID-19. Previous studies in which Candida genotyping was carried out are limited by the fact that the number of isolates was low, they were sourced exclusively from patients with COVID-19, and they were not designed to address the question of clonal spreading as a driver of higher candidemia incidence in COVID-19 patients [ 30 , 31 ]. As a whole, comparison of this population with patients without COVID-19 provides valuable and thorough information not previously described, since comparisons of candidemia episodes including patients with and without COVID-19 have been only occasionally carried out [ 14 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the study performed in Qatar where no association was found between candidemia, including C. auris , and the use of corticosteroids and tocilizumab after matching for the period of LOS in the ICU [ 29 ]. On the contrary, in a study conducted by Rajni et al, the multivariate logistic regression analysis showed that tocilizumab was an independent predictor of candidemia in severe COVID-19 patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariable logistic regression analysis, only LOS and high qSOFA score were shown to be independent risk factors for C. auris isolation. Longer ICU stay had been shown to be a risk factor for the development of candidemia, including C. auris fungemia in several studies, possibly because of horizontal transmission of C. auris during a prolonged ICU stay [ 10 , 26 , 27 , 28 ]. In a case-control study conducted by Omrani et al to assess risk factors for candidemia, including C. auris in COVID-19 patients, 8 out of 82 cases of candidemia were due to C. auris , and qSOFA score in addition to age were shown to be the only independent risk factors for candidemia in COVID-19 patients admitted to the ICU [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation